Evaluating Dropshipping Through Hadith and Islamic Commercial Law: Unauthorized Sales, Salam, and Wakalah bi Al-Ujrah - Nurul Hasanah Simamora; Farid Adnir (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
The expansion of dropshipping has renewed questions in Islamic commercial jurisprudence concerning ownership, authorization, possession, delivery risk, and contractual uncertainty. Although previous studies have examined dropshipping through Islamic jurisprudence and hadith, they have not consistently integrated hadith source mapping and selected transmission issues with a comparative assessment of different contractual models. This article examines three normative configurations: dropshipping conducted without supplier authorization, dropshipping structured as salam, and dropshipping conducted through wakālah bi al-ujrah. It employs focused qualitative library research using major hadith collections, transmitter biographies, classical commentaries, and relevant contemporary studies. The analysis combines takhrīj al-ḥadīth with a focused review of selected transmission issues, textual context, classical commentary, and fiqh al-ḥadīth. The report lā tabiʿ mā laysa ʿindaka appears in several major collections. Al-Tirmidhī classified the report associated with Ḥakīm ibn Ḥizām as ḥasan, while Shuʿayb al-Arnaʾūṭ’s critical edition of Musnad Aḥmad evaluates one transmission route as weak because of a disputed interruption but classifies the report as a whole as ṣaḥīḥ li-ghayrihi on the basis of corroborating evidence. The legal analysis shows that dropshipping cannot be assigned a uniform ruling merely because the seller lacks physical inventory. An unauthorized independent sale raises legal concerns when the dropshipper lacks ownership, contractual authority, and a reliable capacity to deliver. Salam may provide a valid structure when its substantive requirements are fulfilled, while wakālah bi al-ujrah may do so when the mandate, authority, compensation, and responsibilities are clearly defined. The article offers a focused textual-contractual framework for evaluating normative dropshipping models without claiming that particular marketplace practices necessarily comply with them.